Comparative Analysis of Early Postoperative Period in Patients with Total Arterial Revascularization and Conventional Coronary Artery Bypass Grafting - Oleksandr Yu. Pukas; Nadiya M. Rudenko (Ukrainian Journal of Cardiovascular Surgery, 2022)
The use of total arterial myocardial revascularization in patients with multivessel lesions of the coronary arteries has a number of advantages, namely the duration of functioning or patency of the grafts. The level of total arterial myocardial revascularization implementation in developed and developing countries remains quite low.The aim. Based on the analysis of our own experience, to determine the influence of the technique of total arterial revascularization on the frequency of complications in the early postoperative period.Materials and methods. From February 22, 2016 to December 24, 2020, 390 consecutive patients were operated at the Ukrainian Children’s Cardiac Center. The patients were divided into two groups: participants of the group I underwent total arterial myocardial revascularization, and those includedin the group II underwent conventional coronary artery bypass grafting (CABG). The inclusion criteria were: ischemic heart disease, stable angina or exertional angina, multivascular coronary artery disease, absence of valvular pathology.Results. There was zero 30-day mortality in both groups. The frequency of postoperative bleeding was higher in group II and amounted to 1.6%. Surgical wound complications (infection) were also more common in the group II: 1.2% versus 0.69% (p=0.906) in the group I. Similarly, laboratory parameters such as the level of creatine kinase-MB were almost identical.Conclusions. Total arterial myocardial revascularization is a safe method with good immediate results. The frequency of complications in total arterial myocardial revascularizationdoes not differ from that in conventional CABG. For a wider application of the total arterial myocardial revascularization,it is necessary to continue toconduct studies of the remote postoperative period.